Sosialisasi Pentingnya Lembaga Bantuan Hukum pada Masyarakat Desa - Nurhadi, Nurhadi; Haka, Nukhbatul Bidayati; Lestari, Riski Ayu; Muttaqien, Muhammad Aditya; Berlianda, Achmad Daffa; Syalhafiz, Muhammad Thariq; Dewi, Gustianti (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2024)
For people who are economically disadvantaged, Legal Aid Institutions (LBH) play an important role in upholding justice and guaranteeing their access to the legal system. LBH has a very important role in ensuring that human rights enforcement and the legal system operate efficiently in an increasingly complex global context. This socialization activity was carried out by the 131 KKN team as a form of community service because there was still a lack of understanding of the importance of LBH in society. The purpose of this outreach is to provide understanding to the public about the importance of LBH in society to help uphold justice, especially for the less fortunate. This socialization activity was held at the Traditional Hall in Pekondoh Village, Way Lima District, Pesawaran Regency. The method used was to conduct outreach to the Pekondoh Village community with 31 participants. As a result, the participants or the Pekondoh Village community, understood the importance of LBH within the community.